Spectral evolution of the supergiant HMXB IGR J16320-4751 along its orbit using XMM-Newton - García, Federico (2018)
Context. The INTEGRAL satellite has revealed a previously hidden population of absorbed high-mass X-ray binaries (HMXBs) hosting supergiant stars. Among them, IGR J16320-4751 is a classical system intrinsically obscured by its environment, with a column density of ∼10 23 cm -2 , more than an order of magnitude higher than the interstellar absorption along the line of sight. It is composed of a neutron star rotating with a spin period of ∼1300 s, accreting matter from the stellar wind of an O8I supergiant star, with an orbital period of ∼9 days. Aims. We investigated the geometrical and physical parameters of both components of the binary system IGR J16320-4751. Since in systems of this type the compact object is usually embedded in the dense and powerful wind of an OB supergiant companion, our main goal here was to study the dependence of the X-ray emission and column density along the full orbit of the neutron star around the supergiant star. Methods. We analyzed all existing archival XMM-Newton and Swift/BAT observations collected between 2003 and 2008, performing a detailed temporal and spectral analysis of the X-ray emission of the source. We then fitted the parameters derived in our study, using a simple model of a neutron star orbiting a supergiant star. Results. The XMM-Newton light curves of IGR J16320-4751 display high-variability and flaring activity in X-rays on several timescales, with a clear spin period modulation of ∼1300 s. In one observation we detected two short and bright flares where the flux increased by a factor of ∼10 for ∼300 s, with similar behavior in the soft and hard X-ray bands. By inspecting the 4500-day light curves of the full Swift/BAT data, we derived a refined period of 8.99ââ ±ââ 0.01 days, consistent with previous results. The XMM-Newton spectra are characterized by a highly absorbed continuum and an Fe absorption edge at ∼7 keV. We fitted the continuum with a thermally comptonized COMPTT model, and the emission lines with three narrow Gaussian functions using two TBABS absorption components, to take into account both the interstellar medium and the intrinsic absorption of the system. For the whole set of observations we derived the column density at different orbital phases, showing that there is a clear modulation of the column density with the orbital phase. In addition, we also show that the flux of the Fe Kα line is correlated with the N H column, suggesting a clear link between absorbing and fluorescent matter that, together with the orbital modulation, points towards the stellar wind being the main contributor to both continuum absorption and Fe Kα line emission. Conclusions. Assuming a simple model for the supergiant stellar wind we were able to explain the orbital modulation of the absorption column density, Fe Kα emission and the high-energy Swift/BAT flux, allowing us to constrain the geometrical parameters of the binary system. Similar studies applied to the analysis of the spectral evolution of other sources will be useful to better constrain the physical and geometrical properties of the sgHMXB class.